Revisiting Subanen History through Analyses of Flora and Fauna in Subanen Folklore - Paul Omar Gangoso (East Asian Journal of Multidisciplinary Research, 2023)
Given the limited number of available literature on Subanen culture and history, scholars and researchers are drawn to study the monologues of Subanen folklore to extract truthful historical accounts, separating myths from facts. Through the three published epics subject to this study, significant characteristics of Subanen history are identified through the lens of the key flora and fauna. These factual historical references add up to the whole Subanen identity in the Philippines’ diverse cultural and socio-political landscape.